Biological autoluminescence enables effective monitoring of yeast cell electroporation - Bereta, Martin; Teplan, Michal; Zakar, Tomáš; Vuviet, Hoang; Cifra, Michal; Chafai, Djamel Eddine (Biotechnology journal, 2024)
The application of pulsed electric fields (PEFs) is becoming a promising tool for application in biotechnology, and the food industry. However, real-time monitoring of the efficiency of PEF treatment conditions is challenging, especially at the industrial scale and in continuous production conditions. To overcome this challenge, we have developed a straightforward setup capable of real-time detection of yeast biological autoluminescence (BAL) during pulsing. Saccharomyces cerevisiae culture was exposed to 8 pulses of 100 μs width with electric field strength magnitude 2-7 kV cm-1. To assess the sensitivity of our method in detecting yeast electroporation, we conducted a comparison with established methods including impedance measurements, propidium iodide uptake, cell growth assay, and fluorescence microscopy. Our results demonstrate that yeast electroporation can be instantaneously monitored during pulsing, making it highly suitable for industrial applications. Furthermore, the simplicity of our setup facilitates its integration into continuous liquid flow systems. Additionally, we have established quantitative indicators based on a thorough statistical analysis of the data that can be implemented through a dedicated machine interface, providing efficiency indicators for analysis.
Keywords: elektroporace; Saccharomyces cerevisiae; Electroporation